Предмет: Алгебра,
автор: AppleGameplays5
Упростите выражение (а+1)(а-1)(а^2+1)-(9+а^2)^2 и найдите его значение при а=1/3.
Ответы
Автор ответа:
5
(а+1)(а-1)(а²+1)-(9+а²)² = (a²-1)(a²+1) - (9+a²)² = a⁴ -1 - 81 - 18a² - a⁴ = -18a² - 82
Если a = 1/3 то
-18a² - 82 = -18(1/3)² - 82 = -2 - 82 = -84
Похожие вопросы
Предмет: Английский язык,
автор: vladikilicheva
Предмет: Алгебра,
автор: Аноним
Предмет: Химия,
автор: mimimissariasha2019
Предмет: География,
автор: Марина132411
Предмет: Математика,
автор: дашасаша2002